The Leadership FactorThe Leadership Factor, by KotterJohn P.. New York: Free Press, 1988, 161 pp., $19.95, cloth. - Tucker, Sharon A. (Academy of Management Review, 1989)
The article presents a review of the book ?The Leadership Factor,? by John P. Kotter.